Community assembly and functional diversity along succession post‐management. (24th March 2014) - Bhaskar, Radika; Dawson, Todd E.; Balvanera, Patricia; Baltzer, Jennifer
Summary Despite extensive development of successional theory, few empirical studies have evaluated whether existing models are applicable to human‐modified landscapes. Seasonally dry tropical forests are experiencing widespread transformation, and represent a critical system to assess in a successional framework to infer the mechanisms that shape assembly of secondary forests post‐management. We used a functional trait‐based approach to assess changes in community assembly mechanisms along a successional gradient in secondary dry forests of varying stages following abandonment of cattle activity. Nearby old‐growth forests served as an undisturbed comparison. We evaluated whether re‐assembly proceeded consistent with existing theory, in early successional stages via habitat filtering, leading to reduced trait range, and via competitive exclusion in later stages, leading to increased trait evenness. Using three orthogonal traits and two functional diversity indices we tested for evidence of assembly mechanisms along resource axes that may be particularly important to dry forest systems, dynamic changes in habitat filtering and competitive exclusion, and potential legacy effects of management. We found little support of a progression from habitat filtering to competitive exclusion, with the exception of dispersion patterns for specific leaf area and multi‐variate functional richness. Water availability may underlie species sorting in most stages, as evidenced by range reduction in wood density, and might be a resource particularly important to dry forest assembly. Early successional stages displayed an unexpected pattern of low evenness, which may be due to initial stand composition including remnants and resprouts, a regeneration strategy typical to dry forest species. Beyond influencing initial conditions, management legacy was apparent in advanced secondary forests, which differed in range, even dispersion, and functional richness from old‐growth forests, suggesting the operation of different assembly mechanisms. The departures from expectations suggest the need to re‐assess successional models to include effects of management legacies on the operation of community assembly mechanisms in human‐modified landscapes, as well as characteristics that distinguish wet and dry forest dynamics.